Adaptive Consoles for Supervisory Control of Multiple Unmanned Aerial Vehicles - Fuchs, Christian; Ferreira, Sérgio; Sousa, João; Gonçalves, Gil (Human-Computer Interaction. Interaction Modalities and Techniques, 2013)
With the prevailing increase of complex operational scenarios, involving multiple unmanned aerial vehicles (UAV), the concerns with the natural increase of operator workload and reduction of situational awareness have become paramount in order to safeguard operational security and objective completion. These challenges can be tackled through alterations of the autonomy levels of the vehicles, however this paper explores how these issues can also be mitigated by changing the way information is presented to the human operator. Relying upon an established framework, that supports operational scenarios with multiple UAVs, a series of display alterations were performed to existing operation consoles. After test sessions, in a simulated environment, with human participants of different levels of operational certification, feedback and results are distilled and analysed. Operator feedback demonstrated an overwhelming preference for the developed consoles and results showed an improvement of situation awareness, as well as reduction of workload.